Fibropapillomatosis Associated with Chelonid alphaherpesvirus 5 (ChHV5) in a Green Turtle Chelonia mydas in Argentine Waters - Origlia, Javier Anibal (2023)
Fibropapillomatosis is a debilitating neoplastic disease associated with Chelonid alphaherpesvirus 5 (ChHV5) infection. We detected the Atlantic variant of ChHV5 associated with a fibropapilloma in a green turtle (Chelonia mydas) found stranded on the western coast of Rio de la Plata, Argentina. This is the southernmost registered case for the southwestern Atlantic.